2021
DOI: 10.3389/fonc.2021.709579
|View full text |Cite
|
Sign up to set email alerts
|

m6A Regulator-Mediated Methylation Modification Model Predicts Prognosis, Tumor Microenvironment Characterizations and Response to Immunotherapies of Clear Cell Renal Cell Carcinoma

Abstract: BackgroundThis study aims to establish an N6-methyladenosine (m6A) RNA methylation regulators-mediated methylation model and explore its role in predicting prognostic accuracy of immune contexture and characterizations of clear cell renal cell carcinoma (ccRCC).MethodsThe m6A modification subclasses (m6AMS) were identified by unsupervised cluster analysis and three clusters were determined by consensus clustering algorithm in a discovering cohort. Testing and real-world validation cohorts were used to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Recently, N6-adenosine methylation has been found to play a critical role in the tumor immune microenvironment and to be associated with cancer prognosis ( 61 65 ). In fact, N6-adenosine methylation regulates not only the development or function of immune cells and other stromal cells within the TME, but also the responses of the TME to various stimuli, such as hypoxia, internal or external cellular stress, metabolic dysregulation, chronic inflammation, and TGF-β ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, N6-adenosine methylation has been found to play a critical role in the tumor immune microenvironment and to be associated with cancer prognosis ( 61 65 ). In fact, N6-adenosine methylation regulates not only the development or function of immune cells and other stromal cells within the TME, but also the responses of the TME to various stimuli, such as hypoxia, internal or external cellular stress, metabolic dysregulation, chronic inflammation, and TGF-β ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intratumoral and peritumoral TLS also have distinct functions. In intrahepatic cholangiocarcinoma, colorectal cancer, hepatocellular carcinoma, BC, and clear cell renal cell carcinoma, it has been suggested that peritumoral TLS is associated with a worse survival, whereas intratumoral TLS is associated with a favorable prognosis 9,84–87 . However, peritumoral TLS density is associated with higher maturity and anti‐PD‐1 reactivity in esophageal cancer 88 .…”
Section: Forming Process and Immune Mechanisms Of Tlsmentioning
confidence: 99%
“…( 118 ) constructed an m 6 A score to accurately evaluate the m 6 A methylation pattern in ccRCC patients, which could be used to predict the anti-PD-1 treatment response in ccRCC. In ccRCC the high m 6 A score group had higher PD-L1 expression, larger numbers of CD8+ T cells and CD4+ FOXP3+ Treg cells, and higher levels of immune cell infiltration ( 119 ). Among patients receiving immune checkpoint therapies, the clinical benefits were significantly higher in patients with high m 6 A scores ( 119 ).…”
Section: Associations Of M 6 a Rna Methylation With Tumor Immunity In Various Cancersmentioning
confidence: 99%
“…In ccRCC the high m 6 A score group had higher PD-L1 expression, larger numbers of CD8+ T cells and CD4+ FOXP3+ Treg cells, and higher levels of immune cell infiltration ( 119 ). Among patients receiving immune checkpoint therapies, the clinical benefits were significantly higher in patients with high m 6 A scores ( 119 ). The expressions of 17 m 6 A RNA methylation regulators were closely related to the immunity and malignant progression of papillary renal cell carcinoma ( 120 ).…”
Section: Associations Of M 6 a Rna Methylation With Tumor Immunity In Various Cancersmentioning
confidence: 99%